Fireworks and feelings – reaching out creatively to young people through the storm of bereavement. Issue 2 (1st September 2011) - Gardner, Dee; Sullivan, Paul
Abstract : Children and young people are often shielded from the initial trauma of a terminal diagnosis of a parent or significant care giver, resulting in less time to come to terms with an imminent death than older family members. This may affect their bereavement. Fireworks and Feelings children's project encourages early, open support among peers. To enable a sharing of experiences between bereaved young people, using choice and free expression, young people were invited to attend an art day. They used creative arts as a medium for expression within a safe environment with clear expectations and a choice of artistic materials for all levels of ability; we had a shared, social lunch in the middle of the day, and they each chose one art work from the day for display in an exhibition of their works, later, continuing the sharing theme. The day was faciliated by volunteers with support and encouragement to express, with minimal instruction. The follow-up exhibition and celebration is for all participants and their families. A positive experience of peer sharing which extended beyond the day with many of the young people swapping email address and phone numbers. Keeping in touch, sharing, understanding individual grief feelings and developing peer support enhanced well being and psychological health. The Exhibition reunited this group, and shared with family and friends the celebration of the special person and their achievement of expression. Involvement in the arts assists in the development of mental and social health and well-being. It allows freedom of expression and playfulness. Young people create social and psychological bonds and relationships extending beyond the art day. There is exploration and expression of deeper levels, without words, providing an alternative method for those who may struggle to put words to the feelings around such an important and significant loss.